The Analysis The Impact of Net Export, Investment, Labour and Exchange Rate on Economic Growth in Indonesia in The Year of 2000-2020 - Vina Kurniawati (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
Economic growth is defined as an indicator measuring whether a country's economy is progressing or not, especially in Indonesia, due to the high and low levels of production factors for goods and services that will affect economic development. This study aims to determine and an2alyze the extent of the influence of Net exports, Investment, Labor, and Exchange Rates on economic growth from 2000 to 2020. The data used in this study are secondary data obtained from the official website of the Indonesian Central Statistics Agency (BPS). , The Central Bank of Indonesia (BI) and the Indonesian Investment Coordinating Board (BKPM). Researchers tested multiple linear regression analysis with the Ordinary Least Square (OLS) method using Eviews 10 as a testing tool to see the effect of independent variables on the dependent variable. Based on the research conducted by the author, the results show that the factors that influenced economic growth in 2000-2020 were investment, labor and the exchange rate, while net exports had no effect because during the 2000-2020 period the development of net exports in Indonesia was still slower due to growing imports from year to year and low product competitiveness due to export commodities that are still based on primary products that do not have added value From these results, it is hoped that the government will be able to support activities that can encourage net exports through infrastructure development and development of primary commodities into products with high selling value, able to create conducive investment climate , safe and regulatory that not complicated for investors in Indonesia, can provide facilities in order to improve the quality of human resources and also be able to fulfill of labor rights, the government must also be able to provide monetary and fiscal policies that can maintain the stability of the rupiah exchange rate in the global market